COMPETENCE BASED TRAINING IMPLEMENTATION PRINCIPLES - Pitor, Jan; Havel, Karel (Doprava a spoje, 2012)
This paper summarizes the basic principles of competence based training implementation into pilot training. It provides an overview of competence based training features, defines the term ``competency'' and shows the differences of assessment in comparison to conventional types of training. At the end it shows some problems that may be encountered during competence based training construction.